Personal social network of young people in institutional care - Dias, Sandrine (2016)
Aims: The social personal network has been considered an important protection factor when dealing with adversity. This study aims to characterize the social personal network of youngsters in foster homes during extended periods of time, by comparing the results according to sex. Method: Eighty-four youngsters participated in this study, 49 girls and 35 boys, aged between 12 and 20 years old (M = 15.26; SD = 2.17), living in 6 institutions of foster care (Santarém, Portugal). All were assessed through the Personal Social Networks Analysis Tool (characterize the structural, functional, and contextual/relational dimensions of networks). Results: The social network of youngsters in foster care is composed of 12 elements, on average, it is fragmented, diversified, and primarily composed of family members. The level of social support perception is high (emotional and informative function), having a high satisfaction with social support. The contact frequency with the social network members is associated with the geographic distance. Boys have networks slightly bigger than girls and they value more family relations. Girls tend to identify more elements from “friend-families” (p < 0.05), they tend to identify more diverse and denser networks, and they see the relationships as more symmetric (p < 0.05). Girls identify networks mainly feminine and boys tendentiously masculine (p < 0.01).  Boys recognize a higher level of informative support (p = 0.031), companionship (p = 0.040), and access to new contacts (p = 0.001). Conclusions: This study confirms the relevance of family to the young people in foster care, despite the distance, the frequency of contacts, and the underlying reasons that lead them to foster homes. These findings lead us to the importance of understanding the perspective from young people themselves about their interpersonal relationships, in order to enhance the informal social support and to plan a supported autonomization process.